Digital Literacy on Increasing the Pedagogical Competence for Teachers in Primary School - Susilowati, Nola; Haryono, Haryono (Universitas Negeri Semarang, 2025)
Increasing teacher pedagogical competence is one of the key factors in improving the quality of education in primary schools. In the current digital era, digital literacy is an important aspect that teachers must master to support a more effective and efficient learning process. This research aims to analyze the role of digital literacy in improving the pedagogical competence of teachers in elementary schools. This study uses a literature review method by analyzing various relevant literature sources. The findings of this study indicate that digital literacy has a significant impact on the improvement of pedagogical competence of elementary school teachers. Digital literacy can enhance teaching skills, curriculum development skills, classroom management skills, collaboration with other educators, and creativity and innovation of elementary school teachers. Therefore, this study can contribute to the development of digital literacy skills of elementary school teachers and improve the quality of education in Indonesia.